(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Climate change is now a problem of present generation rather than future. In the present era, the resolution of environmental issues should be on the top priorities of all stakeholders of society and efforts should be made to minimize it as much as possible. Delhi is 10th most polluted city of the world and it is facing more environmental problems. Consumers are playing a significant role in society and the over-consumption and over utilisation of the natural resources has led to deterioration of nature (Chen & Chai, 2010). Consumers of millennial generations are more sensitive to sustainability (Kapferer & Michaut-Denizeau, 2020). This Paper emphasis on Green Consumer Behaviour of millennials and the impact of Environmental Consciousness, Environmental Attitude and Perceived Quality of green products on Green Consumer Behaviour of Millennials in NCT of Delhi. A structured questionnaire has been used to record the responses of 230 millennials consumers of NCT of Delhi and SEM technique is used to analyse the significance of all the constructs used in the study. The factors influencing Consumer Behaviour used in various models is considered as the basic idea for study in the light of Green Consumer Behaviour and especially for millennials of NCT of Delhi. The results found that all the factors used in the study have a significant impact on Green Consumer Behaviour. This paper has mentioned the implications for marketers to support the sustainable development of society.